Deteriorating water quality state on the structural assemblage of aquatic insects in a North-Western NigerianRiver. Issue 1 (31st December 2022) - Garba, Fatima; Ogidiaka, Efe; Akamagwuna, Frank C.; Nwaka, Kehi H.; Edegbene, Augustine O
ABSTRACT: Benthic aquatic insects receive the most direct impact when surface waters are perturbed. However, scarce data and understanding about activities' effects on surface water ecosystems remain a critical challenge for water resource managers and policymakers in tropical regions. In this study, we surveyed the implications of deteriorating physical and chemical parameters on aquatic insects' structural assemblage to ascertain the ecological health of River Hadejia in North-Western Nigerian. We sampled aquatic insects and physicochemical parameters in three stations influenced by various land-use activities such as informal settlements and agricultural activities for six months. The two-way analysis of variance (ANOVA) revealed physicochemical parameters such as transparency, depth, and nitrate were not significantly affected by sites' land-use activities ( p > .05) in the six months sampled. However, mean electrical conductivity was lowest in Station 3 (104.3 ±  8.04 µS/cm). Dissolved oxygen (DO), five days biochemical oxygen demand (BOD5 ) values recorded portray a relatively perturbed water system. We recorded four aquatic insects orders belonging to 11 families and taxa. Dytiscus sp. was the most abundant taxon in the study area. A total of 44, 37, and 35 individuals of aquatic insects were recorded in stations 1, 2, and 3 in the river. The Post hoc test performed for all the diversity indices were not significantly different between the studied stations ( p > .05). Canonical correspondence analysis (CCA) revealed poor relationship between the physicochemical parameters and the aquatic insects. However, Gyrinus sp. was positively affected by increased water depth, showing a strong negative association with depth. Cluster analysis revealed that aquatic insects' assemblage structures were mainly grouped by temporal factors (months) rather than spatial differences between the sites. Overall, this study provides further insights and understanding regarding land-use impacts on the ecological health of the River Hadejia, and we recommend more stringent regulations to control human pressure on the river systems within the studied area to enable surface waters in the area to sustain the provision of desired and valued ecosystem services.